Together or side by side in the labour market: generational differences in the working life - Kurai, Marianna; Suhajda, Csilla Judit (Studia Mundi – Economica, 2015)
In our changing world the technology, technological development and innovation efforts appear as an essential part of life characterized by everyday life, but it involves the generational differences and the risk of conflicts. In our work based on McCrindle (2012, 2014) and Kelly studies (2007, 2009, 2012) the goal is to explore the causes and manifestations of the world of work generational tensions experienced. To find the explanation we were examined 3 economically active generation within the framework of the survey about the field of communication differences. By the results we hindering the effective cooperation and conflict resolution and show the best practices about reducing the generation differences.